Effects of fortification of Daqu with various yeasts on microbial community structure and flavor metabolism. (March 2020) - Li, Weiwei; Fan, Guangsen; Fu, Zhilei; Wang, Wenhua; Xu, Youqiang; Teng, Chao; Zhang, Chengnan; Yang, Ran; Sun, Baoguo; Li, Xiuting
Graphical abstract: Highlights: The microbial community structure and related metabolites in the Daqu fermentation process were monitored in real time. Three high yield ethyl caproate producing yeasts were used to fortify Daqu . Fortified Daqu with three high yield ethyl caproate producing yeasts showed lower concentrations of alcohols. Ethyl caproate content was associated with Saccharomyces and Clavispora . Abstract: Fortification of Daqu with isolated functional strains can influence the metabolic activity of the microbial community, and thus alter the flavors of the Baijiu produced with Daqu as a fermentation starter. Here, we analyzed the microbial community dynamics of, and volatile compound production by, Daqu fortified respectively with three high-yield ethyl caproate-producing yeasts ( Saccharomyces cerevisiae Y7#09, Hyphopichia burtonii F12507 and Clavispora lusitaniae YX3307), or with a mixture of these three strains, during the fermentation of Baijiu . The microbial community was investigated using Illumina HiSeq technology. Three bacterial genera ( Bacillus, Lactobacillus and Enterobacter ) and four fungal genera ( Pichia, Clavispora, Saccharomyces and Saccharomycopsis ) were dominant in the microbial communities. The volatile compounds were examined by gas chromatography-mass spectrometry. Forty-one flavor compounds were detected in all samples, including seven alcohols, 26 esters and four aldehydes. In particular, an increase in ethyl caproate content was associated with Daqu fortified with S. cerevisiae Y7#09, C. lusitaniae YX3307, or the mixed inoculum. The ester content of these fortified Daqu was higher in the later stage of the fermentation than that in unfortified Daqu, or in Daqu fortified with H. burtonii F12507. Our results show that fortification of Daqu with aroma-producing yeast strains influenced the microbial community composition in the Daqu and affected its metabolic activity. Overall, this study reveals the features of fortified Daqu microbial communities in different phases and improves understanding of the relationships between aroma-producing yeast and the metabolic activity of microbial communities in Baijiu production.